Composite finite elements on dynamic and buckling responses of composite beams with independent rotations. (November 2022) - Lin, Jian-Ping; Chen, Kun; Zhang, Lei; Huo, Jingsi; Xu, Rongqiao; Wang, Guannan
Abstract: To better understand the structural dynamic response and integrity under complex engineering situations, displacement-based variational principles and corresponding composite finite elements (CFEs) are developed for the simulation of vibration and buckling behavior of partial-interaction composite beams. The accuracy of the composite FEs are validated against the analytical and numerical results in the literature where good agreement is always generated. More importantly, the effect of independent-rotation assumption is investigated in the simulation which is tested to have significant impact on the natural frequencies and buckling loads of composite structures with distinct components and generally lead closer results to the plane-stress FE results. The influence of the rotation of sub-structure on the relative slips between sub-structures is discussed. This explains the discrepancies observed in the literature. The construction of CFEs also considers the internal degrees of freedom (DoFs), which are then eliminated through static condensation, to alleviate the shear/curvature locking phenomenon. The convergence of the proposed FEs are tested, along with the capability of the present FEs in avoiding the locking phenomenon. The final explicit expressions of the elements are also offered and can be readily implemented into the commercial packages with high computational efficiency.